Schrödinger's man: why I want to both die and try : a cognate, historic apology of narratology, structuralist narrative theory and character theory via the gateway of theatre text creation and reception & presenting the play Double Shot - Eisenstein, Craig Martin Fels (My University, 2016)
The present study examines the ways in which a creative text can be created purely through theoretical elements generally first brought to the fore by way of the Russian formalist school of literary thought. Presented with the thesis is a full theatrical play (to be found on page 106) spawned solely as a product of the theoretical tenets set out under the components of structuralist narrative theory - a literary field often referred to as narratology. The play Double Shot is the creative artefact that is built from and inhabits the areas formulated by structuralist thought. Additionally, narratological theory operates as a framework with which to deconstruct the play Double Shot as to determine the efficacy and meaning generated through its precise theoretical provenance. By determining the success, and varying degrees thereof, of Double Shot's finality, it is possible to draw conclusions that a modern formulation of structuralist narrative theory is a viable gateway via which it is possible to generate a creative artefact. By touching on the following processes, Schrödinger’s Man, establishes the pathway for this cognate apology and vindication of narratology. Both the historic forms of formalist narrative theory are considered as well as the different forms of structuralist theory that consequently evolved over several decades. The strident, contemporary applicable elements from various incarnations of the literary theory are highlighted, and the failings, or less congruent elements, are given over to more modern and better fitting considerations. In this way the proposed form of Receptive Narratology is defined and is subsequently used as the primordial soup to give life to the play, Double Shot. Following a modern conceptualisation of narratology, a synopsis of Double Shot is presented, revealing the entire plot of the play while also illustrating several of the key scenes chosen for examination in later chapters. While a full copy of the play is reproduced with the thesis, the inclusion of the synopsis benefits the theory by means of rendering the critical aspects of the play (with its underlying, foundational theories) patently and provides the possibility for the thesis to be read as a standalone work if it were required. Ultimately, all the constituents of structuralist narrative theory are delineated and ordered in their presentation. A narrative text is classified according to its story and its discourse, the story forming the message of play and discourse occupying the mechanisms by which that message is conveyed and altered as it passes to an audience or reader. The story component is further broken into events (plot) and existents (environment) which are finally arrayed into four elements: actions, happenings, characters and settings. Each of these aspects, from action to discourse occupies its own chapter and demonstrates the theory informing its makeup. From this, the technique in appropriating the theory into the creative text's narrative is disclosed and analysed as to its effectiveness. By means of this setup, the modifications required by theory to contort to a theatrical text (which are minor) are given some attention despite the main focus on establishing the puissance of narratology constructing and deconstructing a narrative within a literary modern milieu. The thesis concludes with a declamation that the aegis granted by a modified, contemporary form of structuralist narrative theory is a stalwart armour with which to don a narrative text, for it well safeguards fundamental storytelling techniques and multiple forms of audience interpretation, while fending off barbarous hordes of time-shifting literary forms of text analysis, allowing a classical theory Platonian origins to remain sturdy and sound where modern Gauls abound.
A Thesis and Play submitted to the School of Arts and Faculty of Humanities, University of the Witwatersrand, in fulfilment of the requirements for the Degree of Masters in Drama by Creative Project: Playwriting.